Associated factors for cognition of physically independent elderly people living in residential care facilities for the aged in Sri Lanka - Gamage, M.W.K.; Hewage, Chandana; Pathirana, Kithsiri Dedduwa (My University, 2019)
Attached
Keywords: Elderly people, Cognition, Associated factors